LC-MS/MS-QTOF dataset of compounds detected in kelulut honey of the stingless bees, Heterotrigona itama and Tetrigona binghami from Kuantan, Pahang, Malaysia - Ismail, Che Muhammad Khairul Hisyam; Khong, Nicholas M.H.; Ahmad, Azmir; Mokhtar@Makhtar, Khairani Idah; Lestari, Widya; Mustafa Al-Ahmad, Basma Ezzat; Abdul Hamid, Azzmer Azzar; Mohd Abd Razak, Mohd Ridzuan; Ismail, Azlini (Elsevier, 2023)
Honey is a sustainable nutritious substance which has been incorporated into the human diet since ancient times for its health and remedial benefits. Stingless bee honey or kelulut honey (KH) is well-known in Malaysia and has received high demand in the market due to its distinctive unique flavour. Its composition, colour, and flavour are majorly affected by the geographical location, floral source, climate, as well as the bee species. This data article presents the nontargeted metabolite profiling of the extracts of KH of Heterotrigona itama and Tetrigona binghami bee species. The KH was collected from three nests in Kuantan, Pahang, which is situated in the east coast of Peninsular Malaysia. The extracts were prepared using sugaring-out assisted liquid-liquid extraction (SULLE) method and the Liquid Chromatography–Tandem Mass Spectrometry with Quadrupole Time-of-Flight, operated in the negative ion mode, was used to identify compounds in the extracts. The data processing revealed the presence of 35 known compounds in the KH1 extract by Heterotrigona itama collected from Bukit Kuin, 38 compounds in the KH2 extract by H. itama collected from Indera Mahkota, whilst 50 known compounds were present in KH3 extract by Tetrigona binghami species from Indera Mahkota. This data article contains the m/z values, retention times, and the METLIN database search hit identities of the compounds and their respective classes.